2022
DOI: 10.3847/1538-4357/ac76c3
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of n- and l-resolved State-selective Charge Exchange in Ar8+ Collision with He

Abstract: The state-resolved capture cross sections for principal n and orbital angular momentum l play an important role in modeling soft X-ray emissions induced by charge exchange for many astrophysical environments. However, the empirical and semiclassical theories used to produce these data of n- and l-resolved state-selective capture have not been well tested. Using the cold target recoil ion momentum spectroscopy apparatus at Fudan University, we perform a series of measurements of Ar8+ ion charge exchange with He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…In contrast, it was found that all the existing analytical models to describe CX in astrophysical observations, like separable, even, low-energy, and statistical models, are insufficient to describe the ℓ distributions for the system considered. The present results, together with our recent measurements for Ne 8+ + He and H 2 (Xu et al 2021) and Ar 8+ + He systems (Xia et al 2022), indicate that the applicability of these models should be collision velocity and collision partner species dependent, and the electronic correlations for multielectron processes cannot be neglected.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…In contrast, it was found that all the existing analytical models to describe CX in astrophysical observations, like separable, even, low-energy, and statistical models, are insufficient to describe the ℓ distributions for the system considered. The present results, together with our recent measurements for Ne 8+ + He and H 2 (Xu et al 2021) and Ar 8+ + He systems (Xia et al 2022), indicate that the applicability of these models should be collision velocity and collision partner species dependent, and the electronic correlations for multielectron processes cannot be neglected.…”
Section: Discussionsupporting
confidence: 70%
“…In the case of CX between 4 keV u −1 Ne 8+ and He or H 2 (Xu et al 2021), the measurements are best reproduced by separable and even model calculations, while the fitting to the available data by Gu et al (2016) suggests that ℓ distribution is better represented in the energy region of our concern by a statistical weight. Furthermore, in the most recent study of 1.4-20 keV u −1 Ar 8+ collisions with He (Xia et al 2022), it was shown that none of these models could even approximately describe the measured distributions. This situation indicates that the ℓdistribution may be sensitive to the properties of the collision partners since the analytical models could not give consistent predictions for different collision systems.…”
Section: Model Evaluations For ℓ-Sub-shell Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the collision energy dependence of doubly excited states has been sparsely reported for state-resolved double CX. Recently, with the development of the COLTRIMS detection technique, nlresolved state selectivity in Ar 8+ and C 4+ CX with He has been measured and commonly used n scaling laws and l distributions by astrophysical modelers have been tested (Guo et al 2022;Xia et al 2022). This has significantly advanced studies of state-resolved CX, of which a complete understanding has not been achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Since O q+ (q = 0-8) ions initially are in the keV to MeV range at the upper atmosphere of Jupiter and then slow down as they pass through the atmosphere, CX would be importantly involved during the slowing down of the ions (Schultz et al 2017). Note that with the increase of collision energy the state-selective channels will be squeezed and cannot be well resolved with the COLTRIMS method (Alessi et al 2012;Xu et al 2021;Xia et al 2022). Based on these considerations, the present collision energy range is chosen to be 19.5 to 100 keV amu −1 (i.e., 0.31 to 1.6 MeV), which can contribute to Jupiter's EUV aurora emission induced by O 6+ CX collisions at the transition energy range from intermediate to high.…”
Section: Introductionmentioning
confidence: 99%